Escitalopram and progressive muscle relaxation training are both effective for the treatment of hot flashes in patients with breast cancer: a randomized controlled trial - Maryam Shirzadi; Negin Farshchian; Arash Nazarpour; Soudabeh Eskandari; Fahimeh Kahrari; Hamed Abdollahpour Ranjbar; Somayeh Nazari; Issa Hekmati; Sara Farhang (Taylor & Francis Group, 2022)
Introduction Available treatments for hot flashes in patients with breast cancer are not always tolerable or effective for all patients. Methods Patients diagnosed to have primary breast cancer were randomly allocated to receive 10 mg of escitalopram, placebo, or progressive muscle relaxation therapy. Patients were asked to report the frequency and duration of hot flashes during day and night, at baseline and after ten weeks of treatment, and completed the menopause rating scale. Results Eighty-two patients were randomly assigned to receive escitalopram (n = 26), PMRT (n = 28), and placebo (n = 28). PMRT and escitalopram could effectively decrease number and duration of diurnal and nocturnal HFs in patients with breast cancer, with a better effect observed from escitalopram. They could both decrease the total score of MRS. Conclusion Both escitalopram ad PMRT can reveal nocturnal and diurnal HFs in terms of frequency and duration in patients with breast cancer.